Effectiveness of Artificial Intelligent Independent Learning (AIIL) with physics chatbot of global warming concept - Alfarizi Ade Karlin Kusuma; Winne Aulia Dyah Maharani; Firmanul Catur Wibowo; Hadi Nasbey; Bayram Costu (Universitas PGRI Kanjuruhan Malang, 2024)
This research aims to analyze the effectiveness of Artificial Intelligent Independent Learning (AIIL) with physics chatbot of global warming concept. Method of research uses the Research & Development method referring to the ADDIE development model. This research was conducted with 64 students at Senior High School in Indonesia who were divided into chatbot-based experimental groups and control groups. The results of this study were obtained by conducting the normalized gain <g> test of 0.60 (medium category) for the control group and 0.87 (high category) in the experimental group. As for the results of the Cohen's D effect-size test, the result was 0.93 with high category AAIL for increasing learning outcome. Thus, the developed AAIL chatbot has high effectiveness in increasing learning outcome.